Anchoring in experimental asset markets - Sascha Baghestanian; Todd B. Walker (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
We investigate the relationship between anchoring and the emergence of bubbles in experimental asset markets. We show that setting a visual anchor at the fundamental value (FV) in the first period only is sufficient to eliminate or to significantly reduce bubbles in laboratory asset markets. If no FV-anchor is set, bubble-crash patterns emerge. Our results indicate that bubbles in laboratory environments are primarily sparked in the first period. If prices are initiated around the FV, they stay close to the FV over the entire trading horizon. Our insights can be related to initial public offerings and the interaction between prices set on pre-opening markets and subsequent intra-day price dynamics.
Keywords: C90; C91; D03; G02; G12; 330; Experimental Asset Markets; Anchoring; Bubbles